FIXED ANTIHYPERTENSIVE DRUGS COMBINATION SELECTION WITH THE AIM OF ORGANS PROTECTION - O. D. Ostroumova; I. I. Kopchenov; O. V. Bondarets; T. F. Guseva (Российский кардиологический журнал, 2015)
The article focuses on the problems of choice among the antihypertension drugs combinations according to organs protection properties. It is underlined that target organs damage (microalbuminuria, pulse wave rate velocity increase, myocardial hypertrophy of the left ventricle, atherosclerotic plaques in carotid arteries) are independent predictors of cardiovascular mortality. Optimal combinations of antihypertension drugs are reviewed taking kidney damage, vessel wall damage, the heart and the brain. The data provided on organs protective properties of lercanidipine, enalapril and fixed combination of them.